Determining the appropriate use of Technology Enabled Care Services (TECS) to manage upper-limb trauma injuries during the COVID-19 pandemic: A multicentre retrospective observational study. Issue 7 (July 2022) - Sayed, L.; Valand, P.; Brewin, M.P.; Matthews, A.; Robson, M.; Nayaran, N.; Alexander, A.; Davies, L.; Scott, E.; Steele, J.; McMullen, E.
Summary: Background: The COVID-19 pandemic created a unique opportunity to explore the use of Technology Enabled Care Services (TECS), which remains novel for many service providers. This study assesses the factors that affect adaptation to remote monitoring of patients after upper-limb trauma injury. A standardised risk-stratified screening tool is further developed here to support clinical staff in both the determination of appropriate use of TECS and the optimisation of patient care. Objectives: 1: To explore the patient and injury factors that determine the appropriate use of TECS for patients with upper-limb injury. 2: To use these findings to refine a standardised screening tool for the appropriate choice of follow-up format. Methods: A retrospective review of patient management was undertaken across three NHS upper-limb trauma units during the first UK COVID-19 lockdown. Data were collected, and themes were analysed across a number of predetermined categories. This was underpinned by a review of contemporary policy guidance and literature. Results: A total of 85% of patients were offered an appropriate format of follow-up; this was defined by the ability to achieve desired patient-clinician goals and lack of complications. Key factors in determining appropriate follow-up included extent of injury, mental health considerations, and the need for face-to-face (F2F) assessment and treatment. Conclusion: Study findings demonstrate consistency between units in the factors determining the appropriate use of TECS. The refined screening tool provides a risk-stratified, standardised approach to the choice of follow-up format, F2F or TECS. It is hoped that this will support future clinical decision-making processes to ensure optimal patient care.